ANALISIS KEBUTUHAN PESERTA DIDIK TERHADAP E-LKPD INTERAKTIF BERBASIS INQUIRY LEARNING PEMBELAJARAN IPAS KELAS V - Tia Komala Sari; Anggit Merliana; Asep Nuryadin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the needs of students for the development of interactive E-LKPD based on inquiry learning in learning IPAS grade V, especially on the topic "Economic Conditions in My Region". The research used a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation studies. The research subjects included educators and fifth grade students in one of the elementary schools in Tasikmalaya City. The results showed that students need teaching materials that are contextual, interactive, and in accordance with technological developments. Learning is still dominated by conventional LKPDs that are less interesting and have not applied the inquiry approach optimally. Interactive E-LKPD with an inquiry learning approach is considered capable of answering these needs because it can facilitate active learning, increase motivation, and strengthen concept understanding. Therefore, the development of interactive E-LKPD based on inquiry learning is a strategic step to improve the quality of IPAS learning in elementary schools.